2009
DOI: 10.1152/ajpendo.90544.2008
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous transplantation of embryonic pancreas for correction of type 1 diabetes

Abstract: Islet transplantation is a promising therapeutic approach for type 1 diabetes. However, current success rates are low due to progressive graft failure in the long term and inability to monitor graft development in vivo. Other limitations include the necessity of initial invasive surgery and continued immunosuppressive therapy. We report an alternative transplantation strategy with the potential to overcome these problems. This technique involves transplantation of embryonic pancreatic tissue into recipients' s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…It has been shown that donor islets transplanted into the livers of patients with type I diabetes can result in complete insulin independence within weeks 6. Recent studies have shown that subcutaneous islet transplants are capable of normalizing blood glucose homeostasis and achieving endocrine differentiation and vascularization 7. Hence islets are capable of what appears to be normal function in an environment of non-native tissue.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that donor islets transplanted into the livers of patients with type I diabetes can result in complete insulin independence within weeks 6. Recent studies have shown that subcutaneous islet transplants are capable of normalizing blood glucose homeostasis and achieving endocrine differentiation and vascularization 7. Hence islets are capable of what appears to be normal function in an environment of non-native tissue.…”
Section: Introductionmentioning
confidence: 99%
“…7 Islet transplantation is a promising treatment that has been shown to reverse the effects of islet loss in type 1 diabetes, yet further research is needed to enhance islet survival and to address the immune reaction of transplant recipients. 8,9 Most research to date has focused on the insulin-secreting β-cells within islets, which helps to ensure blood glucose homeostasis. However, recent work has highlighted the importance of paracrine communication among the multiple cell types within the islet, 10,11 indicating a need for more refined methods in studying the multicellular architecture of islets and its relation to function.…”
mentioning
confidence: 99%
“…The possibility of regulating blood glucose using a physiological combination of alternate hormones was first suggested in our early studies, where subcutaneous transplants of embryonic pancreatic tissue resulted in correction of chemically induced T1D with no accompanying increase in insulin 38 , 39 . Diabetic mice who received embryonic pancreatic transplants made a complete and permanent recovery with no detectable increase in the insulin response, exhibiting proliferation of WAT and increased plasma levels of adipokines instead.…”
Section: Reversal Of T1d With Batmentioning
confidence: 99%